أثر حركة السوائل في التخامد - محمد غانم (Tishreen University, 2018)
Structures which have Fluid containers in the upper section can dissipate a main part of the entered vibration energy when subjected to dynamic loads by free surface vibration energy، the movement of free surface waves participate in dissipating structural vibrating energy. This research has discussed the fluid movement problem when subjected to seismic vibration، and its role in decreasing dynamic response structure. Elevating tanks were accredited in this study due to the fact that the engineering shape of such structures shows the impact of fluid-movement on the dynamic response. Using SAP2000 program، time history analysis for two seismic records which are Elcentro ، Kope . We concluded that the increase of the area of free surface of fluid induces more quantity of fluid to vibrate ، and consequently dissipate more quantity of entered energy.   تمتلك المنشآت التي تحتوي على مستوعبات سائلة في الأجزاء العلوية منها القدرة على تبديد جزأ هام من طاقة الاهتزاز المدخلة إلى المنشأة عند التعرض للتحريض الديناميكي وذلك بفعل طاقة اهتزاز السطح الحر للسائل حيث أن حركة الأمواج على السطح الحر يساهم في تبديد جزأ من طاقة اهتزاز المنشأة. ناقش هذا البحث مسألة حركة المياه عند التعرض للاهتزاز الزلزالي ودورها في تقليل الاستجابة الديناميكية للمنشآت حيث تم اعتماد نموذج الخزانات العالية في الدراسة كون أن الشكل الهندسي لهذه المنشآت يظهر بشكل كبير أثر حركة السائل على الاستجابة الديناميكية. تم الاعتماد على برنامج SAP2000 والتحليل باستخدام طريقة السجل الزمني لزلزالين هما السنترو وكوبي. وقد تم الاستنتاج في الختام أنه مع زيادة مساحة السطح الحر يحرض كمية أكبر من المياه على الاهتزاز وبالتالي تبديد كمية أكبر من الطاقة المدخلة.